Methylation of the hypoxanthine phosphoribosyltransferase locus on the human X chromosome: implications for X-chromosome inactivation. - Wolf, S F (1984)
To explore the role of DNA methylation in maintaining dosage compensation of X chromosome-linked genes and in regulating the transcriptional activity of "housekeeping" genes, we characterized DNA methylation of active, inactive, and derepressed alleles at the locus for hypoxanthine phosphoribosyltransferase (HPRT) on the human X chromosome. The methylation of Hpa II and Hha I sites in HPRT alleles on the active X chromosome was the same in all tissues. The consensus pattern includes hypomethylation of 5' clustered sites and extensive methylation of the 3' sequence. The striking feature of methylation of inactive X-chromosome alleles is nonuniformity and less extensive hypomethylation of the 5' cluster. Analysis of HPRT alleles reactivated in response to 5-azacytidine showed at least partial restoration of the consensus pattern. These observations indicate that methylation of housekeeping genes on the X chromosome is the same as that of autosomal ones and that the overall pattern and methylation of multiple sites within a cluster may cooperate to facilitate transcription. Furthermore, the fidelity of methylation of the active allele and the extensive drift in methylation of the inactive allele suggest that mechanisms involved in X-chromosome dosage compensation may be directed at the active rather than inactive X chromosome.